The Digital Divide: Telemedicine with AI vs. The Traditional In-Person Visit - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The landscape of healthcare delivery is undergoing a profound transformation, driven by the convergence of telemedicine and Artificial Intelligence AI. This ...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Medical Ethics